Analysis of the Effect of Tourist Facilities and Accessibility on Intention to Revisit Through Trust as an Intervening Variable on Sarangan Lake Tourism - Oksatana, Miga; Halik, Abdul; Fianto, Achmad Yanu Alif (PT Inovasi Pratama Internasional, 2025)
One of the main industries that support the Indonesian economy is tourism, which has enormous potential. One of them is Telaga Sarangan tourism, located on the slopes of Mount Lawu, Plaosan District, Magetan, East Java.This study aims to analyze the effect of tourism facilities and accessibility on interest in revisiting Telaga Sarangan tourism, with trust as an intervening variable. A quantitative approach is used in this study is. The population in this study was Bank Jatim employees who visited tourist attractions. The sample consisted of 100 employees. The analysis method used was Partial Least Square structural equation modeling (PLS-SEM) using SmartPLS 4.0. The results of the study showed that 1) tourism facilities had a significant effect on trust, with a path coefficient value of 0.432 and a p-value of 0.022 (<0.05). 2) Accessibility had a significant effect on trust, with a path coefficient of 0.450 and a p-value of 0.006 (p<0.05). 3) Tourism facilities did not have a significant direct effect on the intention to revisit, with a path coefficient of 0.024 and a p-value of 0.887 (>0.05). 4) Accessibility does not have a significant effect on the intention to revisit, with a path coefficient of 0.097 and a p-value of 0.540 (> 0.05); 5) trust has a significant effect on the intention to revisit, with a path coefficient of 0.725 and a p-value of 0.000 (< 0.05); 6) trust mediates the relationship between tourism facilities and the intention to revisit, with a path coefficient of mediation of 0.314 and a p-value of 0.044 (< 0.05); and 7) trust mediates the relationship between accessibility and the intention to revisit, with a path coefficient of mediation of 0.326 and a p-value of 0.016 (< 0.05)